Superior Hardness Of Zirconia Toughened Aluminaceramics Through Co-Addition Ofmagnesium Oxide Andlanthanum Oxide - Kong, Chee Xian (Universiti Sains Malaysia, 2018)
MgO addition into Zirconia toughened Alumina (ZTA) shown a positive impact on Vickers hardness (1710 HV) but only reduced the indentation fracture resistance (KIFR) (3.38 MPa.√m). The low KIFR originated from the formation MgAl2O4 phase in the ZTA /MgO system decreased the KIFR of the ceramics due to the low intrinsic indentation fracture resistance of MgAl2O4. To develop a high performance cutting insert, the ceramics must acquire both high hardness and KIFR value. Hence, addition of La2O3 in ZTA seem to be an approach as La2O3 are capable of improving the KIFR of alumina-based ceramics. The mixtures were prepared with addition of La2O3 (0.1 wt.% to 10.0 wt.%) to ZTA/1.0 wt.% MgO. The mixtures were pressed to a rectangular bar at 1600 ºC for 4 hours to observe its effect on microstructure, phases formation, density, porosity and finally measurement of hardness and KIFR. From the hardness and KIFR result obtained, optimization was carried out to tune with the addition of La2O3 content (0.7 wt.% - 1.0 wt.%) for better KIFR with slight reduction of the hardness value. The addition of La2O3 shown a significant effect on the formation of finer Al2O3 grains, creating strong interface between the Al2O3 grains and LaAl11O8 grains result in denser ZTA/MgO ceramics of hardness of 2028 HV. Also, the presence of rod like LaAl11O8 grains in the ZTA/MgO ceramics improved the KIFR up to 6.67 MPa.√m.